Discovery in Balinese Shadow Puppet Shows - I Made Marajaya (RIRAI Publisher, 2023)
The purpose of this article is to examine discovery in relation to the creativity of Balinese shadow puppet show agents. Since time immemorial, there has been nothing new in the creativity of Balinese shadow puppet shows. However, it turns out that there is novelty and discovery in the development of Balinese shadow puppet shows. The problems are: 1) Why does the puppeteer innovate in the Balinese shadow puppet show?; 2) What is the form of discovery in the Balinese shadow puppet show?; 3) Is there an impact of discovery in the Balinese shadow puppet show? This problem has been investigated using qualitative methods. Discovery elements related to creativity in Balinese shadow puppet performances have been observed, and a literature study has been carried out based on publications about Balinese shadow puppets. All data were analyzed qualitatively using practical theory and aesthetic theory from a cultural studies perspective. The results of the study show that: 1) responding to market demands, cultural influences from modern society, technological sophistication, and the need for creativity and artist training for Balinese shadow puppet performances; 2) there is a condensation of the performance structure accompanied by a simplification of the language of the puppeteers, variations in the movements of the puppet characters, variations of light, variations of sound, and new apparatus are discoveries in Balinese shadow puppet performances; and 4) the discovery of the Balinese shadow puppet show has had an impact on Balinese puppet artists and art. Keywords : Discovery, Creativity, Shadow Puppet Show, Bali.